Expedited SARS‐CoV‐2 screening of donors and recipients supports continued solid organ transplantation. Issue 11 (23rd June 2020) - Lieberman, Joshua A.; Mays, James A.; Wells, Candy; Cent, Anne; Bell, Deborah; Bankson, Daniel D.; Greninger, Alexander L.; Jerome, Keith R.; Limaye, Ajit P.
Abstract : Universal screening of potential organ donors and recipients for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is now recommended prior to transplantation in the United States during the coronavirus disease 19 (COVID‐19) pandemic. Challenges have included limited testing capacity, short windows of organ viability, brief lead time for notification of potential organ recipients, and the need to test lower respiratory donor specimens to optimize sensitivity. In an early U.S. epicenter of the outbreak, we designed and implemented a system to expedite this testing and the results here from the first 3 weeks. The process included a Laboratory Medicine designee for communication with organ recovery and transplant clinical staff, specialized sample labeling and handoff, and priority processing. Thirty‐two organs recovered from 14 of 17 screened donors were transplanted vs 70 recovered from 23 donors during the same period in 2019. No pretransplant or organ donors tested positive for SARS‐CoV‐2. Median turnaround time from specimen receipt was 6.8 hours (donors), 6.5 hours (recipients): 4.5 hours faster than daily inpatient median. No organ recoveries or transplantations were disrupted by a lack of SARS‐CoV‐2 testing. Waitlist inactivations for COVID‐19 precautions were reduced in our region. Systems that include specialized ordering pathways and adequate testing capacity can support continued organ transplantation, even in a SARS‐CoV‐2 hyperendemic area. Abstract : A system prioritizing SARS‐CoV‐2 testing for candidate organ transplant donors and recipients supports continued transplantation, even in a period of high prevalence and before rapid diagnostic platforms are available.